A meso–meso β‐β β‐β Triply Linked Subporphyrin Dimer. Issue 40 (23rd August 2017) - Okuda, Yasuhiro; Fukui, Norihito; Kim, Jinseok; Kim, Taeyeon; Jiang, Hua‐Wei; Copley, Graeme; Kitano, Masaaki; Kim, Dongho; Osuka, Atsuhiro
Abstract: A meso–meso β‐β β‐β triply linked subporphyrin dimer6 was synthesized by stepwise reductive elimination of β‐to‐β doubly Pt II ‐bridged subporphyrin dimer9 . Dimer6 was characterized by spectroscopic and electrochemical measurements, theoretical calculations, and picosecond time‐resolved transient absorption spectroscopy. X‐ray diffraction analysis reveals that6 has a bowl‐shaped structure with a positive Gaussian curvature. Despite the curved structure, 6 exhibits a remarkably red‐shifted absorption band at 942 nm and a small electrochemical HOMO–LUMO gap (1.35 eV), indicating an effectively conjugated π‐electronic network. Abstract : A triply linked subporphyrin dimer was synthesized by stepwise reductive elimination of a β‐to‐β doubly Pt II ‐bridged subporphyrin dimer with the concurrent formation of the meso–meso bond. Despite the curved structure, the triply linked dimer displayed a remarkably red‐shifted absorption spectrum and narrow electrochemical HOMO–LUMO gap because of the effectively conjugated π‐electronic network.